"Greening out" Treating cannabis-related problems in the ED. Issue 6 (November 2017) - Murphy, Kathryn
Abstract : Emergency visits are on the rise as states legalize recreational marijuana. Abstract : Emergency visits are on the rise as states legalize recreational marijuana.